2019
DOI: 10.1021/acs.inorgchem.9b00651
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Stability and Cationic Nonstoichiometry of CuFeO2 Delafossite

Abstract: CuFeO 2 , the structure prototype of the delafossite family, has received renewed interest in recent years. Thermodynamic modeling and several experimental Cu−Fe−O system investigations did not focus specifically on the possible nonstoichiometry of this compound, which is, nevertheless, a very important optimization factor for its physicochemical properties. In this work, through a complete set of analytical and thermostructural techniques from 50 to 1100°C, a fine reinvestigation of some specific regions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 72 publications
3
17
1
Order By: Relevance
“…[11][12][13][14][15][16][17][18] High-quality epitaxial Cu 1+ Fe 3+ O 2 thin films without the presence of impurities containing Cu 2+ ions would be a preferable platform to study the fundamentals of physical and chemical properties of this material. However, the heteroepitaxial growth of high-quality and impurity-free CuFeO 2 thin film turns out to be a formidable challenge owing to the complex thermodynamics and nonstoichiometry, and the coexistence of multiple phases in the Cu-Fe-O solid solution [19][20][21][22] as well as the metastable nature of the Cu 1+ cation in complex oxide compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] High-quality epitaxial Cu 1+ Fe 3+ O 2 thin films without the presence of impurities containing Cu 2+ ions would be a preferable platform to study the fundamentals of physical and chemical properties of this material. However, the heteroepitaxial growth of high-quality and impurity-free CuFeO 2 thin film turns out to be a formidable challenge owing to the complex thermodynamics and nonstoichiometry, and the coexistence of multiple phases in the Cu-Fe-O solid solution [19][20][21][22] as well as the metastable nature of the Cu 1+ cation in complex oxide compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 2 shows the phase diagram of the CueFeeO system calcu lated using Factsage software from the thermodynamic model published Shishin et al [49] and by Schorne Pinto et al [48] for an oxygen pressure pO 2 10 À5 atm which corresponds to the pO 2 measured in the furnace during the annealing in this work. Based on previous experimental tests done under air and argon atmo sphere, the copper solubility in the delafossite structure is extrap olated in this plot at x 0.47.…”
Section: Atomic Compositionmentioning
confidence: 94%
“…Trofimov [47] have already reported such copper non stoechiometry in undoped copper iron delafossite, but without any structural proof of the presence of the pure delafossite phase. Schorne Pinto et al [48] have recently demonstrated that the delafossite structure can accept a copper excess up to 14% in air, i.e. up to x 0.53 before any precipitation of copper single oxide.…”
Section: Atomic Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, above 673 K, the structure of delafossite CuFeO 2 decomposes according to the following reaction: 2Cu I Fe III O 2 + 1 2 O 2 ! Cu II Fe III 2 O 4 + CuO (Schorne-Pinto et al, 2019). In most cases, during the synthesis of copper ferrite by any method, the 3R polytype (rhombohedral phase), with more or less content of the 2H polytype (hexagonal phase), is formed.…”
Section: Introductionmentioning
confidence: 99%